AI and Uncertain Motivation: Hidden allies that impact EFL argumentative essays using the Toulmin Model - Abdullah Al Fraidan (Acta Psychologica)
This study investigates the combined impact of artificial intelligence (AI) tools and Uncertain Motivation (UM) strategies on the argumentative writing performance of Saudi EFL learners, using the Toulmin Model. Sixty Saudi EFL students participated in four writing tasks, with results demonstrating significant improvements in essay quality, particularly in clarity, structure, and depth. AI tools provided real-time feedback, enhancing students' ability to refine claims, data, backing, and counterarguments. UM strategies, employing varied and unpredictable rewards, effectively sustained student motivation and engagement. However, a temporary decline was noted early in the study, attributed to the learning curve associated with both AI and the Toulmin model.Writing argumentative essays poses significant linguistic and cognitive challenges for EFL learners. By addressing these barriers, the study highlights the potential of AI to enhance EFL writing proficiency and underscores the motivational role of UM in maintaining student engagement. The findings emphasize the importance of integrating AI and UM thoughtfully into educational practices to maximize their effectiveness. Future research is encouraged to explore AI's long-term effects, address ethical considerations, and refine the integration of AI and UM strategies across diverse learning contexts.